Sejarah Perkembangan Pemikiran Politik Islam dari Masa Klasik hingga Kontemporer - Mega Rahmayani AS; Nurlela Abbas; Mahmuddin Mahmuddin (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2026)
The discussion of Islamic politics remains a crucial issue due to the long-standing dynamics of debate within the reality of Muslim-majority countries. This article aims to deeply explore the transformation of Islamic political ideas and their utility in a modern context through a comprehensive historical review. The scope of this study encompasses the trajectory of thought from the classical period, rooted in the leadership of Prophet Muhammad SAW in Medina, to the development of the political spectrum in the contemporary era. Utilizing a descriptive qualitative research method based on literature studies and content analysis techniques, this article dissects various historical documents and the works of key thinkers to map the shifts in power paradigms. The research findings indicate that in the classical era, Islamic politics was understood as a comprehensive system uniting religion and state through the codification of fiqh siyasah, even as the leadership structure shifted from democratic to absolute monarchy. Conversely, in the contemporary period, Islamic political discourse has transformed to be more contextual and profane by integrating issues of modernity such as democracy, human rights, and nation-state sovereignty. The ongoing dialectic between past normative traditions and present-day needs forms a dynamic intellectual mosaic, proving the resilience of Islamic politics in addressing governance challenges both globally and within the local Indonesian context.